Review and Prospects of Pathogen Detection Related to Autopsy of Coronavirus Infectious Diseases - WANG Yun-yi, ZHOU Nan, YUE Jia-cheng, et al. (Fayixue Zazhi, 2021)
In the past, coronavirus caused two serious human-to-human pandemics in the world, including severe acute respiratory syndrome （SARS） and Middle East respiratory syndrome（MERS）. In late 2019, coronavirus disease 2019 （COVID- 19） caused another major global public health event. Due to the strong infectivity of novel coronavirus, it is difficult to carry out the autopsy of related death cases widely. This paper reviews the previous status of the pathogen detection related to the autopsy of coronavirus infection diseases, and introduces the ongoing detection methods of novel coronavirus in clinical practice, in order to provide reference for the pathogen detection and study related to autopsy of COVID-19.